Purchasing decisions: The effects of electronic word-of-mouth, product quality, and price - Kristianto, Victorio Anandito (Universitas Ahmad Dahlan, 2024)
Purpose-Every individual certainly wants to take care of their body to keep looking attractive. Currently, there are many types of cosmetic brands for body care. This raises various considerations for consumers when making purchases. Multiple factors influence consumer purchasing decisions. This study analyzes purchasing decisions influenced by electronic word-of-mouth, product quality, and price. Design/Methodology/Approach-The research sample was the entire community of Indonesia, who had purchased skincare products, totaling 90 respondents. The research sampling technique was purposive, and a questionnaire was distributed via Google Forms. Then, this research used SPSS to process the data. Findings-This study proves that only one of the three hypotheses developed is accepted. Electronic word-of-mouth has no positive effect on purchasing decisions. Product quality is proven to have a positive impact on purchasing decisions. Price is proven to have no positive effect on purchasing decisions. Research limitations/implications-The limitation of this study is that the number of respondents is still relatively small, so it needs to be increased. The research object is also still relatively specific, namely users of skincare products in Indonesia rather than users of skincare products in various regions of Indonesia. Therefore, the results of this study cannot represent the purchasing decisions of users of skincare products in general. Originality/value-This research is relatively rare among previous researchers, who used the users of skincare products in Indonesia, as the research object. Previous studies generally used skincare products of different brands or from other regions as their object of study.